(untitled) (Communication & Society, 2022)
The preference for online social interaction has been seen as an antecedent for problematic use of the Internet and social networks, which is associated with problems of social anxiety and a lack of social skills. Based on a survey with a representative sample of 524 students in Compulsory Secondary Education (aged 12-14) in the Autonomous Region of Madrid (Spain), the role of motives of use as a factor that explains the problematic use of the Internet has been analysed as a mediating component between such problematic use and the preference for online social interaction. The results show that only when social networks are used to expand relationships and as a form of self-expression are there negative consequences for the individual, but not when such networks are used to maintain close relationships. Finally, is has been observed that such motives, which moderately predict problematic use, only slightly explain in part the relationship between the preference for online social interaction and problematic use. Therefore, further research is needed to investigate other motives for use that mediate this association, as well as the connection between the motive to expand social relationships together with self-expression, and other pre-existing personality factors that might lead to problematic use of the Internet and social networks.